Description Of The Traumatic Experience Of The Dinar Indah Housing Flood Disaster Victims - Audrey Eleanor Yuliana Azury Mangimbulur; Azzahra Nurmaliza Putri; Ghea Farah Fahira; Maria Angelina Krista; Adiwena, Bartolomeus Yofana (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
Unpredictable natural disasters can traumatize a person and disrupt the victim's daily activities. Moreover, if this is the first time a victim has experienced a natural disaster. The trauma that arises and the impact on them will be different from the victims who have experienced several natural disasters. In this case, the researcher will provide an overview of the trauma experienced by flood victims who have only experienced floods once, a total of four people. This study uses qualitative data collection techniques using interviews, observation and phenomenological data analysis techniques. The results showed that natural disasters that occurred to participants caused trauma due to this unpleasant experience. This impacts participants who are more easily anxious and afraid when symptoms of natural disasters appear—looking at the results of the interviews in analyzing the symptoms of trauma felt by the participants and how disturbing they were in carrying out their daily activities.